Assessing Vaccination Prioritization Strategies for COVID-19 in South Africa Based on Age-Specific Compartment Model - Zuo, Chao; Meng, Zeyang; Zhu, Fenping; Zheng, Yuzhi; Ling, Yuting (Frontiers in Public Health, 2022)
The vaccines are considered to be important for the prevention and control of COVID-19, however, considering the limited vaccine supply within an extended period of time in many countries where COVID-19 vaccine booster shot (three dose) are taken and new vaccines are developed to suppress the mutation of virus, designing an effective vaccination strategy is extremely important to reduce the number of deaths and infections. Then, the simulations were implemented to study the relative reduction in morbidity and mortality of vaccine allocation strategies by using the proposed model and actual South Africa’s epidemiological data. Our results indicated that in light of South Africa’s demographics, vaccinating older age groups (>60 years) largely reduced the cumulative deaths and “0-20 first” strategy was the most effective way to reduce confirmed cases. Given the daily testing volume and infection rate, “0-20 first” and “60+first” are still the optimal vaccination strategies to reduce the number of confirmed cases and cumulative deaths, respectively. However, comprehensive reduction in infections was mainly affected by the vaccine proportion of the target age group, increasing in the proportion of vaccines given priority to “0-20” groups always had a favorable effect, and the prioritizing vaccine allocation among 60+ age group with 50% of the total amount of vaccine consistently resulted in the greatest reduction in deaths. Meanwhile, we observed significant distinction in the effect of COVID-19 vaccine allocation policies under varying priority strategy on relative reductions in the effective reproduction number. Our results could help evaluate to control measures performance and improve vaccine allocation strategy on COVID-19 epidemic.